Nekatere geografske značilnosti selitev slovenskih športnikov in športnih delavcev - Gobec, Matic (Šport (Ljubljana), 2016)
The contribution is analyzing the migration of Slovene athletes and sports professionals. Athletes and sports professionals represent a particular social group, which is characterized by a high degree of mobility. The migrations are a part of their everyday life. For sport migrants are common to both temporary and permanent migration. In the last case, the participants must face the naturalization or assimilation in a new environment, while amongthe temporary migrantsć adjustments are sufficient. The study focused on the place and time component of sports migration. The main working method was an online survey sent to Slovene athletes and sports professionals, sports organizations and clubs, with which there were established contacts previously. The main results of the study show a markedly high mobility of Slovene sports migrants. In addition to the most common daily and weekly migration, the seasonal migrations are also very common. The main target areas for immigration of Slovene athletes and sports workers are dispersed primarily within Europe, but are also present in other parts of the world. These migrations therefore have a global dimensions and have slight tendency to increase.
Keywords: družbena geografija; migration; selitve; Slovenia; Slovenija; social geography; sport; šport; športni delavci; športniki